Analisis Kegiatan Pembelajaran Pendidikan Matematika pada masa Pandemic COVID-19 di Negara Asia (Indonesia, Jepang dan Filipina) - jonathan simanjuntak (Sepren, 2021)
The purpose of this study was to obtain information about learning activities for mathematics education during the Covid-19 pandemic in Asian countries (Indonesia, Japan and the Philippines). This study used a literature review method. Sampling was carried out using random sampling. In this study, related respondents were Asian countries including Indonesia, Japan and the Philippines. The Covid-19 pandemic has brought significant changes in the world of learning. The differences in these conditions are interesting to study to provide an overview of what is happening in the country and can be used as an evaluation in the future. This study was conducted through literature studies with various sources, both journals and online news. The selected countries are Indonesia, Japan and the Philippines. The selection is done randomly without any background representing the existing continents. Based on the results of the study, it is known the responses, strategies and obstacles that occurred in the education sector during the pandemic. The strategies, successes, and obstacles that occurred in each country were influenced by the readiness of infrastructure and human resources, as well as the initial conditions of the country before the pandemic.